А это верное условие? Нигде не ошиблись во втором уравнении?
Была ошибка,исправила.

Ответы и объяснения

2014-04-04T11:47:13+00:00
 \left \{ {{(x+1)^{2}-(x-1)^{2} \geq 12} \atop {(x+4)(x-4)-(x+2)^{2}<9}} \right.
Воспользуемся формулами
 a^{2}-b^{2}=(a-b)(a+b)
(a+b)^{2}=a^{2}+2ab+b^{2}
\left \{ {{(x+1-(x-1))(x+1+x-1) \geq 12} \atop {x^{2}-16-(x^{2}+4x+4)<9}} \right.
\left \{ {{4x \geq 12} \atop {-20-4x<9}} \right.
\left \{ {{x \geq 3} \atop {-4x<29}} \right.
\left \{ {{x \geq 3} \atop {x>-7.25}} \right.
Ответ: x \geq 3